EPIDEMIOLOGIC EVALUATION OF THYROID DISEASES MORBIDITY OF UKRAINIAN ADULT POPULATION FROM 2000 TO 2013 - Antonenko, A. M.; Korshun, M. M.; Vavrinevych, O. P.; Omelchuk, S. T.; Bardov, V. H. (International Journal of Medicine and Medical Research, 2018)
Background. The diseases of thyroid gland have been attracting considerable attention in recent decades. This is partly due to the fact that thyroid gland reacts actively to geochemical state and pollution of the environment with industrial and agricultural waste products with the subsequent incidence of certain pathological processes. The objective of the research was to analyze the morbidity of adult population of Ukraine for thyroid gland diseases in the period from 2000 to 2013. Methods. The methods of empirical and theoretical research of scientific information: analysis, synthesis, induction, deduction and systematization, as well as epidemiological and statistical methods were used. Using the Microsoft Office Excel (2007) and IBM SPSS StatisticsBase v.22 program the correlation and regression analyzes were conducted. Results. From 2000 to 2013, high levels of adult population endocrinopathies, thyroid in general and diffuse goiter of varying degrees, general and primary morbidity were registered in the western and northern regions of Ukraine, low – in the central, eastern and southern regions. Statistically significant (p<0.001) positive correlation between the level of prevalence and the level of incidence of endocrine pathology, diseases of thyroid gland as a whole, as well as individual nosology was detected. Conclusions. Regional peculiarities of the levels and dynamics of changes in the incidence rates of thyroid morbidity among adult population of Ukraine can be related to the urgent environmental factors for each region. This factor requires further study to develop effective methods of prophylaxis and defense.